Long-Term Photo-Identification Reveals the Population Dynamics and Strong Site Fidelity of Adult Whale Sharks to the Coastal Waters of Donsol, Philippines ... : يكشف تحديد الصور على المدى الطويل عن الديناميكيات السكانية وإخلاص الموقع القوي لأسماك قرش الحوت البالغة إلى المياه الساحلية في دونسول، الفلبين ... - Emer McCoy; Raul B. Burce; David David; Q. Elson; Jennifer Hardy; Jessica Labaja; Sally Snow; Alessandro Ponzo; Gonzalo Araújo (OpenAlex, 2018)
Donsol in the Philippines is the longest running community-based whale shark (Rhincodon typus) ecotourism site in Southeast Asia, with peak visitation in 2012 of over 27,000 tourists. In order to understand this aggregation and the importance of the area to whale sharks, dedicated photographic identification (photo-ID) research began in 2007. In-water photo-ID surveys were conducted from tourism boats, weather and operator permitting, from December to June between 2007 and 2016. Visual matches of the unique spot patterns of each individual shark were validated by the pattern-recognition software Interactive Individual Identification System (I3S), and on the online database Wildbook for Whale Sharks (www.whaleshark.org). A total of 1,985 photo-ID trips over 895 survey days resulted in 6,786 encounters with R. typus. Combined with encounters from both dedicated research and citizen science dating back to 1998, 479 individual whale sharks were identified, making up 44% of the known whale shark population in the ... : دونسول في الفلبين هو أطول موقع للسياحة البيئية لقرش الحوت المجتمعي (Rhincodon typus) في جنوب شرق آسيا، مع ذروة زيارة في عام 2012 لأكثر من 27000 سائح. من أجل فهم هذا التجميع وأهمية المنطقة لأسماك قرش الحوت، بدأ البحث المخصص للهوية الفوتوغرافية (photo - ID) في عام 2007. تم إجراء استطلاعات صور الهوية في المياه من قوارب السياحة والطقس والسماح للمشغلين، من ديسمبر إلى يونيو بين عامي 2007 و 2016. تم التحقق من المطابقات المرئية لأنماط البقعة الفريدة لكل سمكة قرش فردية من خلال برنامج التعرف على الأنماط نظام التعرف الفردي التفاعلي (I3S)، وعلى قاعدة البيانات عبر الإنترنت Wildbook for Whale Sharks (www.whaleshark.org). أسفر ما مجموعه 1,985 رحلة بهوية مصورة على مدى 895 يومًا من المسح عن 6,786 مقابلة مع R. typus. جنبا إلى جنب مع لقاءات من كل من البحوث المخصصة وعلم المواطن التي يعود تاريخها إلى عام 1998، تم تحديد 479 من أسماك قرش الحوت الفردية، والتي تشكل 44 ٪ من عدد أسماك قرش الحوت المعروفة في الفلبين (العدد = 1095). ومن بين هذه الصور، أكدت صور لمنطقة الحوض جنس 158 من الذكور و 22 من الإناث. تراوحت تقديرات الحجم المرئي من ...